宋玉《神女赋》对曹植《洛神赋》的影响 = The influence of Song Yu's "Shen Nv Fu" towards Cao Zhi's "Luo Shen Fu" - 蔡庭芳 Chua, Ting Fang (2011)
在中国文学史上，以‘神女’作为题材之作品繁多，而宋玉（公元前290-公元前223）可说是以‘神女’为题材作‘赋’的开山祖师，其中以《高唐赋》和《神女赋》最具代表性；此后类似题材的文学作品层出不穷。曹植（公元192-232）《洛神赋》被誉为是模仿宋玉《神女赋》的翘楚。因此，本文欲通过宋玉《神女赋》探讨它对曹植《洛神赋》的影响。首先，将分别研究宋玉《神女赋》及曹植《洛神赋》，并针对作者生平、文本及神女的形象作为主要论点。其次，将针对作者的怀才不遇找出两人的相似之处；再者，根据《神女赋》中的高唐神女到曹植《洛神赋》中洛水女神的形象进行探讨。最后，总观宋玉《神女赋》对曹植《洛神赋》的影响。In the History of Chinese Literature, the topic of ‘Goddess’ had always been common and widely used among the vast variety of Chinese Literature writings. ‘Song Yu’ (BC290-BC223) can be considered as the pioneer who have used and applied the topic of ‘Goddess’ in his literature works. Two of his masterpieces literature writings with the title of “Gao Tang Fu” and “Shen Nv Fu” are the ones that appears to be symbolic, following after this, the number of literature works with the similar nature starts to increase dramatically. Cao Zhi’s (AD192-232) “Luo Shen Fu” is one of the famous articles which is said to imitate the style of writing in Song Yu’s “Shen Nv Fu”. The main aim of this thesis is to observe the impact brought by Song Yu’s “Shen Nv Fu” to Cao Zhi’s “Luo Shen Fu”. Starting off by critically analyzing both Song Yu’s “Shen Nv Fu” and Cao Zhi’s “Luo Shen Fu” individually and focusing largely on the author’s life history, literature works and the image of Goddess. Secondly, identifies the analogy and the similarities between both authors’ miserable life journey. Not only that, making further discussions and comparisons for the perception on the topic ‘Goddess’ in both ‘Gao Tang Goddess’ and ‘Luo Shui Goddess’. Lastly, a detailed conclusion on the impact done by Song Yu’s “Shen Nv fu” towards Cao Zhi’s “Luo Shen Fu”.